LGBTQ Intimate Partner Violence : Lessons for Policy, Practice, and Research - Messinger, Adam M., 1982- (Book collections on Project MUSE., 2017)
Nationally representative studies confirm that LGBTQ individuals are at an elevated risk of experiencing intimate partner violence. While many similarities exist between LGBTQ and heterosexual intimate partner violence, research has illuminated a variety of unique aspects of LGBTQ intimate partner violence regarding the predictors of perpetration, the specific forms of abuse experienced, barriers to help-seeking for victims, and policy and intervention needs. This book systematically reviews the literature regarding LGBTQ intimate partner violence, draws key lessons for practice and policy, and recommends research areas and enhanced methodologies.--description provided by publisher.